Roles of the monoaminergic system in the antidepressant effects of ketamine and its metabolites. (1st February 2023) - Ago, Yukio; Yokoyama, Rei; Asano, Satoshi; Hashimoto, Hitoshi
Abstract: While the molecular target of ( R, S )-ketamine (ketamine) is thought to be the NMDA receptor, subanesthetic doses of ketamine have been known to modulate monoaminergic neurotransmission in the central nervous system. Although the involvement of the serotonergic system in the antidepressant effects of ketamine has been reported in most studies of this topic, some recent studies have reported that the dopaminergic system plays a key role in the effects of ketamine. Additionally, several lines of evidence suggest that the antidepressant-like effects of ( R )-ketamine might be independent of the monoaminergic system. Ketamine metabolites also differ considerably in their ability to regulate monoamine neurotransmitters relative to ( S )-ketamine and ( R )-ketamine, while ( 2R, 6R )-hydroxynorketamine might share common serotonergic signaling mechanisms with ketamine. In the current review, we summarize the effects of ketamine and its metabolites on monoamine neurotransmission in the brain and discuss the potential roles of the monoaminergic system in the mechanism of action of ketamine. This article is part of the Special Issue on 'Ketamine and its Metabolites'. Highlights: Ketamine and its metabolites have potential for the treatment of depression. Subanesthetic doses of ketamine modulate monoamine neurotransmission in the brain. Neurochemical effects of ketamine and its metabolites are stereoselective. The brain monoaminergic system contributes to ketamine's antidepressant actions.